THE EFFECTIVENESS OF ARCS ( ATTENTION, RELEVANCE,CONFIDENCE AND SATISFACTION) MODEL TO IMPROVE STUDENTS' LISTENING COMPREHENSION - Riskayani; Saiful; Hilda hafid (English Language Teaching Methodology, 2022)
The aims of this study to find out the effectiveness of Using ARCS (Attention, Relevance, Confidence and Satisfaction) model to improve students’ listening comprehension at eleventh grade of SMAN 9 Makassar. In this research was a Descriptive Quantitative research which used experimental research by applying random sampling technique. The samples of the research were the eleventh grade students of SMAN 9 Makassar consisted of 25 students XI.MIA 4. The researcher used one group pre-test post-test design. This research was not control group. In the first step, the researcher gave pre-test and gave eight meetings treatment with narrative text material. After the researcher did the treatment, the researcher gave the students post-test.This research findings were the value of pretest to post-test was higher. Before treatment the value of pretest was 70.6, but after the treatment, the mean score of student post-test was 89.8. The result also showed the improvement of student’s listening increased 21.38 %. It showed that t-test > value was higher than t-table 7.08>2.0. So, the conclusion is H0 was rejected and H1 was accepted, the effect of ARCS (Attention, Relevance, Confidence and Satisfaction) model to improve students’ listening comprehension is effective.